Effect of sea ice on seismic collapse-resistance performance of wind turbine tower based on a simplified calculation model. (15th January 2021) - Huang, Shuai; Huang, Mingming; Lyu, Yuejun; Xiu, Liwei
Abstract: Sea ice is one of the main loads on a wind turbine tower in ice-prone area and threatens the safe working life of the wind turbine tower; however, design codes at home and abroad do not provide a method of calculation for the coupling of the structure, ice, water, and earthquake. In our study, we considered the sea ice and water as the added masses and proposed a simplified calculation model of the dynamic interaction of the water, sea ice, and wind turbine tower under earthquake action, which could avoid the solution of complex non-linear equations and reduce the computational burden. The dynamic balance equation of the simplified calculation model was established, and the effect of the sea ice on the seismic collapse-resistance performance of the wind turbine tower was investigated. The research results show that the failure rate of the wind turbine tower under the influence of ice increases to more than 50%, and we suggested that the seismic fortification intensity should be raised by more than one degree when undertaking seismic design of a wind turbine tower under the influence of sea ice; in addition, the collapse margin ratio of the wind turbine tower fails to meet the demands when the ice thickness is more than 0.6 m. Finally, a shaking table test was conducted to investigate the dynamic interactions of the water, sea ice, and wind turbine tower under earthquake action, and the accuracy of the calculation results of our proposed simplified calculation model was verified.